2018
DOI: 10.1007/s11682-018-9873-5
|View full text |Cite
|
Sign up to set email alerts
|

DTI-derived indexes of brain WM correlate with cognitive performance in vascular MCI and small-vessel disease. A TBSS study

Abstract: Indexes derived from diffusion tensor imaging (DTI) are sensitive to changes of both T2-hyperintense and normal-appearing brain white matter (WM) in elderly subjects with variable cognitive status. We investigated correlations between global cognitive performance and DTI-derived indexes along the WM tracts in the brain of patients with vascular mild cognitive impairment (MCI) and small vessel disease (SVD). Seventy-six patients with vascular MCI and SVD were assessed through Montreal Cognitive Assessment (MoCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…However, in this study, we found no correlation between the DTI derived index and cognition, which was inconsistent with previous studies [14,16,17,39]. This may be related to the fact that our enrolled subjects are mostly preclinical patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in this study, we found no correlation between the DTI derived index and cognition, which was inconsistent with previous studies [14,16,17,39]. This may be related to the fact that our enrolled subjects are mostly preclinical patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Among different methods used in DTI research, trace-based spatial statistics (TBSS) is a reliable and optimized one that minimizes registration errors and personal evaluation biases, and is considered to improve sensitivity, objectivity, and interpretability when applied to multiple diffused data [13]. To our knowledge, there have been a number research on the change of WM microstructural integrity in WMH patients and its correlation with cognition [14][15][16][17]. However, few TBSS studies have directly identified differences in diffusion measurements between patients with varying degrees of WMH.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies provided conflicting or negative results, the periventricular but not subcortical group of the WML, considered as a whole, were found by a systematic review to be correlated in older adults with the executive function and processing speed (Bolandzadeh et al, 2012) and linked, in a 10-year longitudinal study, with a faster general cognitive decline over time (De Groot et al, 2002). In terms of the damage to normal-appearing WM in VMCI, which was recognized for the first time a few years ago with the application of diffusion tensor imaging (DTI) (Maillard et al, 2011), a recent DTI work from our study group highlighted its contribution for the global cognitive performance of these patients (Mascalchi et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…However, our imaging findings revealed no correlation between the MoCA score and FA value. One study reported that the MoCA score positively correlated with the FA value of the corpus callosum ( Mascalchi et al, 2019 ). We speculate that the reason for this discrepancy is the susceptibility of the experimental results to bias due to our small sample size.…”
Section: Discussionmentioning
confidence: 99%